Glacier mass balance Hallstätter Gletscher, Dachstein, Austria, 2023/2024 - Giulia Bertolotti; Klaus Reingruber; Kay Helfricht; Andrea Fischer (PANGAEA, 2025)
The annual glacier mass balance of Hallstätter Gletscher in Austria is measured since 1.10.2006 with the direct glaciological method in the fixed date system (1.10. to 30. 09. of the following year). The accumulation of snow is measured by determination of the water equivalent in 6 snow pits, the ice ablation is measured with 15 stakes drilled into the ice. Results are the annual net mass balance in kg, the total accumulation and ablation, the glacier area and the portions of the area which are subject to ablation and accumulation, the elevation of the equilibrium line and the specific mass balance in kg/m^2 (= mm w.e.). The accumulation during the winter is determined by the 1 May. The project is funded by the Federal Government of Upper Austria. The measurements are carried out the Institute for Interdisciplinary Mountain Research of the Austrian Academy of Sciences and the company Blue Sky in Gmunden, Austria.
In: Fischer, Andrea; Stocker-Waldhuber, Martin; Hartl, Lea; Reingruber, Klaus; Helfricht, Kay (2016): Glacier mass balances and elevation zones of Hallstätter Gletscher, Dachstein, Austria, 2006/2007 et seq [dataset publication series]. Institut für Interdisziplinäre Gebirgsforschung der Österreichischen Akademie der Wissenschaften, Innsbruck, PANGAEA, https://doi.org/10.1594/PANGAEA.806609